(untitled) (Research, Society and Development, 2022)
The application of Industry 4.0 technologies and concepts in industrial logistics processes is an efficient strategy to reduce operating costs, speed up deliveries and increase the efficiency of the enterprise. Thus, this work aims to carry out the conceptual design of an automated logistics system involving the movement, storage and management of packaged products in a furniture industry. The elaboration of this project used the first two stages of the project development methodology proposed by Pahl, Beitz, Feldhusem and Grote (2005), the planning phase and the conception phase. These steps made it possible to prepare the list of requirements, obtain and evaluate the solution variants and present the conceptual design of an automated logistics system based on Industry 4.0 and Logistics 4.0 technologies through the identification of products by radiofrequency and movement by autonomous mobile robots. Aiming at the fabrication and implementation of this conceptual project, two more steps of the methodology of Pahl et al. (2005), the preliminary design phase and the detailed design phase. These steps will define the technical specifications of the equipment and the details of how the transporters, the storage system and the management software work, culminating in the detailed layout of the automated logistics system. Thus, the project has the potential to leverage the growth of the furniture industry, as it will provide an increase in the storage and transport capacity of products independently of human activity and will guarantee the traceability of products in real time.